2016
DOI: 10.1080/2162402x.2015.1093276
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D- and T-cell receptor-dependent lysis of malignant glioma cell lines by human γδ T cells: Modulation by temozolomide and A disintegrin and metalloproteases 10 and 17 inhibitors

Abstract: The interaction of the MHC class I-related chain molecules A and B (MICA and MICB) and UL-16 binding protein (ULBP) family members expressed on tumor cells with the corresponding NKG2D receptor triggers cytotoxic effector functions in NK cells and γδ T cells. However, as a mechanism of tumor immune escape, NKG2D ligands (NKG2DLs) can be released from the cell surface. In this study, we investigated the NKG2DL system in different human glioblastoma (GBM) cell lines, the most lethal brain tumor in adults. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 60 publications
2
55
0
Order By: Relevance
“…S1 and S2). NKG2DL induction by TMZ has previously been reported in four other human glioma cell lines (52). We found that the NKG2DL induction was independent from cytotoxic or growth inhibitory effects and was achieved at clinically relevant concentrations of chemotherapeutic agents and low doses of IR.…”
Section: Discussionsupporting
confidence: 78%
“…S1 and S2). NKG2DL induction by TMZ has previously been reported in four other human glioma cell lines (52). We found that the NKG2DL induction was independent from cytotoxic or growth inhibitory effects and was achieved at clinically relevant concentrations of chemotherapeutic agents and low doses of IR.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, zoledronate is commonly used for osteoporosis in post-menopausal women, thus it would be a suitable therapeutic tool in triggering the immune response in cancer and influencing MSC behavior. More importantly, selective inhibitors of ADAMs, which block the secretion of NKG2D-L from carcinomas, leukemic cells, and MSC, could be used to enhance tumor cell recognition [35,159]. These findings would suggest that MSC display several molecular targets suitable for therapy but no one of them is exclusively expressed by this cell population.…”
Section: Drugs That Can Influence Msc-mediated Immune Regulationmentioning
confidence: 99%
“…Several kinds, compositions, and modes of administration of anti-tumor vaccines have been used with different results [160,161,162,163,164,165,166,167]. More recently, the focus of anti-tumor vaccines has been moved from tumor cells to TME too [7,9,10,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175]. Indeed, the possibility of targeting tumor endothelial cells or the VEGF signaling axis with specific vaccines has been assessed in preclinical studies, and clinical trials are ongoing [168].…”
Section: Msc As Target Cells For Anti-tumor Vaccinesmentioning
confidence: 99%
“…Although shedding caused by the proteolytic activity of a disintegrin and metalloproteinase domain-containing protein (ADAM-10 and 17) regulated expression of ULBP2 (29), reduced expression of NKG2D-L by vemurafenib likely involves another mechanism. We showed that the reduction of ULBP2 on the cell surface of vemurafenib-treated melanoma cells was not due to shedding.…”
Section: Discussionmentioning
confidence: 99%